ANALISIS HASIL PRESTASI BELAJAR SISWA PADA PEMBELAJARAN PJOK DENGAN KURIKULUM MERDEKA DI SMKN 1 JAYAKERTA - Kuntoro Aji; Ine Rahayu Purnamaningsih; Akhmad Dimyati (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The reason for this research is the enactment of a circular regarding the implementation of the Merdeka Curriculum in the context of restoring learning in educational units in the 2022/2023 school year. This study aims to determine the Analysis of Student Learning Achievement Results in PJOK Learning with the Independent Curriculum at SMKN 1 Jayakerta. The research approach uses a quantitative descriptive approach with a survey research method. The population in this study were all class X students of SMKN 1 Jayakerta totaling 291 students. The sampling technique used in this study was cluster random sampling technique, the number of samples in this study were 75 students. Data collection in this study is by questionnaire / questionnaire in the form of statements about learning achievement factors and indicators in the independent curriculum. The Microsoft Excel program is used for data processing in this study. The results showed that the Analysis of Student Learning Achievement Results in PJOK Learning with the Independent Curriculum at SMKN 1 Jayakerta, overall the highest frequency was at the 'medium' level of 34.67%, then the 'very high' level of 6.67%, at the 'high' level of 29.33%, at the 'low' level of 22.67%, at the 'very low' level of 6.67%.